Market Orientation, Learning Orientation and Innovation Performance: The Mediation of Knowledge Management - Ni Made Wahyuni; I Gusti Ayu Ketut Giantari (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
Internationalization of small and medium enterprises (SMEs) contributes as a driver of the economy. It is important for SMEs to produce innovation performance. The aim of the study was to investigate the relationship between market orientation (MO), learning orientation (LO), and knowledge management (KM) on innovation performance. The research method is a cross-sectional research design. The population include export-oriented manufacturing SMEs, registered with the Bali Province Industry and Trade Office (2019). A total of 94 senior SME managers participated in the survey. Partial least square (PLS) based structural equation model was used to test the hypothesis. Finding, KM plays a mediating role in the relationship between MO and LO on innovation performance. Managers’ policies in the practice of strategic orientation and knowledge management strengthen innovation performance.